2021
DOI: 10.1038/s41598-021-97446-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of progression pattern and associated risk factors in glaucoma patients with initial paracentral scotomas using Humphrey 10-2

Abstract: Central visual field (VF) progression could directly threaten patientss visual function compared to glaucomatous damage. This study was designed to investigate visual field (VF) progression pattern and associated risk factors including optical coherence topography angiographic (OCT-A) findings in glaucoma patients with initial paracentral scotoma. This prospective, observational study included 122 eyes presenting as initial paracentral scotomas with serial 24-2 and 10-2 VF tests at the glaucoma clinic of Seoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…The progression rate of MD in the HFA 10-2 should vary depending on the studied population and the disease conditions. David et al reported that the MD slope differed with or without disc hemorrhage (− 0.50 and − 0.15 dB/year, respectively) 42 , while Kim et al reported that the MD slope of eyes with primary open angle glaucoma (POAG) was − 0.11 dB/year, while that with normal tension glaucoma was − 0.33 dB/year 43 in their prospective studies. On the other hand, Wang et al reported that the average MD slope was − 0.37 dB/year in a recent retrospective study 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The progression rate of MD in the HFA 10-2 should vary depending on the studied population and the disease conditions. David et al reported that the MD slope differed with or without disc hemorrhage (− 0.50 and − 0.15 dB/year, respectively) 42 , while Kim et al reported that the MD slope of eyes with primary open angle glaucoma (POAG) was − 0.11 dB/year, while that with normal tension glaucoma was − 0.33 dB/year 43 in their prospective studies. On the other hand, Wang et al reported that the average MD slope was − 0.37 dB/year in a recent retrospective study 44 .…”
Section: Discussionmentioning
confidence: 99%
“…В другом исследовании было доказано, что у многих пациентов с ГНД отмечаются выраженные флуктуации перфузионного давления, которые являются достоверным предиктором ухудшения ПЗ при ГНД [52]. Важным фактором риска прогрессирования ГНД, связанным с парацентральными скотомами, является снижение плотности микроциркуляторного русла сетчатки [53].…”
Section: особенности полей зрения при глаукоме нормального давленияunclassified
“…Evaluations of the quality of vision (QOV) have been used to determine the quality of life (QOL) in glaucoma patients. Although there are various factors related to the QOV in glaucoma patients, 1 it has been shown that there was a high correlation between the retinal sensitivity and the QOV at the fixation point and the inferior region of the visual field. 2–4 …”
Section: Introductionmentioning
confidence: 99%